ChemInform Abstract: Self‐Assembly of Nanostructured Materials Through Irreversible Covalent Bond Formation. Issue 43 (October 2015) - Baek, Kangkyun; Hwang, Ilha; Roy, Indranil; Shetty, Dinesh; Kim, Kimoon
Abstract Review: 47 refs.